Global Survey and Genome Exploration of Bacteriophages Infecting the Lactic Acid Bacterium Streptococcus thermophilus - McDonnell, Brian; Mahony, Jennifer; Hanemaaijer, Laurens; Neve, Horst; Noben, Jean-Paul; Lugli, Gabriele A.; Ventura, Marco; Kouwen, Thijs R.; van Sinderen, Douwe (Frontiers in Microbiology, 2017)
Despite the persistent and costly problem caused by (bacterio)phage predation of Streptococcus thermophilus in dairy plants, DNA sequence information relating to these phages remains limited. Genome sequencing is necessary to better understand the diversity and proliferative strategies of virulent phages. In this report, whole genome sequences of forty distinct bacteriophages infecting S. thermophilus were analysed for general characteristics, genomic structure and novel features. The bacteriophage genomes display a high degree of conservation within defined groupings, particularly across the structural modules. Supporting this observation, four novel members of a recently discovered third group of S. thermophilus phages (termed the 5093 group) were found to be conserved relative to both phage 5093 and to each other. Replication modules of S. thermophilus phages generally fall within two main groups, while such phage genomes typically encode one putative transcriptional regulator. Such features are indicative of widespread functional synteny across genetically distinct phage groups. Phage genomes also display nucleotide divergence between groups, and between individual phages of the same group (within replication modules and at the 3’ end of the lysis module) - through various insertions and/or deletions. A previously described multiplex PCR phage detection system was updated to reflect current knowledge on S. thermophilus phages. Furthermore, the structural protein complement as well as the antireceptor (responsible for the initial attachment of the phage to the host cell) of a representative of the 5093 group was defined. Our data more than triples the currently available genomic information on S. thermophilus phages, being of significant value to the dairy industry, where genetic knowledge of lytic phages is crucial for phage detection and monitoring purposes. In particular, the updated PCR detection methodology for S. thermophilus phages is highly useful in monitoring particular phage group(s) present in a given whey sample. Studies of this nature therefore not only provide information on the prevalence and associated threat of known S. thermophilus phages, but may also uncover newly emerging and genomically distinct phages infecting this dairy starter bacterium.